Efficacy of Fetal Stem Cell Transplantation in Autism Spectrum Disorders: An Open-Labeled Pilot Study. Issue 1 (January 2014) - Bradstreet, James Jeffrey; Sych, Nataliia; Antonucci, Nicola; Klunnik, Mariya; Ivankova, Olena; Matyashchuk, Irina; Demchuk, Mariya; Siniscalco, Dario
Autism spectrum disorders (ASDs) are heterogeneous complex neurodevelopmental pathologies defined by behavioral symptoms, but which have well-characterized genetic, immunological, and physiological comorbidities. Despite extensive research efforts, there are presently no agreed upon therapeutic approaches for either the core behaviors or the associated comorbidities. In particular, the known autoimmune disorders associated with autism are appealing targets for potential stem cell therapeutics. Of the various stem cell populations, fetal stem cells (FSCs) offer the potent immunoregulatory functions found in primordial mesenchymal stem cells, while exhibiting rapid expansion capacity and recognized plasticity. These properties enhance their potential for clinical use. Furthermore, FSCs are potent and implantable "biopharmacies" capable of delivering trophic signals to the host, which could influence brain development. This study investigated the safety and efficacy of FSC transplantations in treating children diagnosed with ASDs. Subjects were monitored at pre, and then 6 and 12 months following the transplantations, which consisted of two doses of intravenously and subcutaneously administered FSCs. The Autism Treatment Evaluation Checklist (ATEC) test and Aberrant Behavior Checklist (ABC) scores were performed. Laboratory examinations and clinical assessment of adverse effects were performed in order to evaluate treatment safety. No adverse events of significance were observed in ASD children treated with FSCs, including no transmitted infections or immunological complications. Statistically significant differences ( p < 0.05) were shown on ATEC/ABC scores for the domains of speech, sociability, sensory, and overall health, as well as reductions in the total scores when compared to pretreatment values. We recognize that the use of FSCs remains controversial for the present. The results of this study, however, warrant additional investigations into the mechanisms of cell therapies for ASDs, while prompting the exploration of FSCs as "biopharmacies" capable of manufacturing the full array of cell-signaling chemistry. This manuscript is published as part of the International Association of Neurorestoratology (IANR) special issue of Cell Transplantation .